Biodiversity at Volvo Group Real Estate Identification of a suitable biodiversity framework and action plan for enhanced biodiversity - Brunke, Julia (My University, 2024)
This master’s thesis was done by request of Volvo Group Real Estate (VGRE) in Gothenburg, Sweden. The aim of this master’s thesis was to decide upon a framework for biodiversity assessment and to develop an action plan for biodiversity for VGRE. A literature study in which criteria was found in order to identify a suitable biodiversity assessment framework was conducted. In addition, a field study, during which an assessment of VGRE:s approach to biodiversity was made. The field study took place at the VGRE site in Tuve, Sweden. The research questions in this master’s thesis gained insight into the data needed when performing a biodiversity assessment and which framework for biodiversity assessment that is most suitable for VGRE. They also investigated what the direct drivers of biodiversity loss that VGRE:s site in Tuve contributes to, how VGRE can reduce their negative impact on biodiversity at their site in Tuve and what actions that can be put in place in order to enhance and/or restore biodiversity at the site. During the master’s thesis it was found that a recurring issue for businesses and industries is that there are many variables and corresponding complications when performing biodiversity assessments. The frameworks for biodiversity assessments, developed by various organisations (both governing and independent), are more complicated than they make light of. There is a certain level of knowledge and expertise needed to implement and/or supplement the frameworks used for biodiversity assessments. The literature and field study was iterative and the selected framework was Biodiversity Net Gain (BNG). In addition, the framework should be able to handle time and resource constraints that may appear while leaving space for the inclusion of tools for continuous reassessment and evaluation. Therefore, in addition to BNG the company will need to adhere to the Mitigation Hierarchy. It was also suggested that the company will use the State, Pressure and Result (SPR) framework to find suitable indicators to monitor their efforts in a quantifiable way. The criteria that the selected framework needed to adhere to was decided upon during both the literature study and the field study. The action plan was divided into two parts, one for areas that are to be exploited and one for areas that are already exploited. In addition, good principles, are included as guidelines for the company to follow.
Keywords: Biodiversity; Biodiversity Assessment; Ecosystem Services; Biodiversity Net Gain; Mitigation Hierarchy; Sweden; Genetic Diversity; Real Estate; Framework; Biodiversity Enhancement and Restoration